Tuberculosis Situation in Children and Adolescents in the Siberian Federal District in 2020-2022 - I. V. Pavlenok; N. V. Tursunova; N. V. Stavitskaya (Туберкулез и болезни лёгких)
The objective:  analysis of tuberculosis epidemiological rates in children and adolescents in the Siberian Federal District in 2020-2022.Subjects and Methods. Offi  cial statistical reporting data (Forms No. 30, 33, 8, and 61) and additional information requested from the regions of the Siberian Federal District were used for analysis.Results.  In 2020 in the Siberian Federal District, tuberculosis incidence among children and adolescents aged 0–17 falsely reduced, possibly due to the «deprivation» of the medical care during the COVID-19 pandemic.  In 2021 and 2022, the rate increased, there was an increase in the proportion of new patients in the group of 0–14 years old, an increase in the number of cases of secondary tuberculosis which may indicate a deterioration of tuberculosis situation in the District. In 2022, the incidence of extrathoracic tuberculosis increased in adolescents aged 15–17 years. The number of cases of TB/HIV co-infection is growing. There are single lethal cases due to tuberculosis in children in the regions of the Siberian Federal District over the past 5 years, and this rate continues to decline.